The healthy migrant effect and predictors of perinatal depression. Issue 3 (June 2019) - King, Leonora; Feeley, Nancy; Gold, Ian; Hayton, Barbara; Zelkowitz, Phyllis
Abstract: Problem: Although prenatal depression is a risk factor for postpartum depression, current screening tools for prenatal depression fail to predict postpartum depression in some marginalized populations. Background: The assessment of other risk factors along with prenatal depression may be needed to improve prediction of postpartum depression and these risk factors may be specific to immigrants. Aims: We investigated the predictive utility of several measures in relation to postpartum depressive symptoms in: recent immigrants, less recent immigrants and Canadian-born women. Methods: Measures pertaining to psychosocial risk factors, generalized anxiety, perinatal somatic and depressive symptoms were administered. Data were collected at 4 time-points: 12–14 weeks and 24–28 weeks gestation as well as 1-week and 8-weeks postpartum. Perinatal factors were entered into 3 different regression models to predict postpartum depressive symptoms at the last time-point. Findings: Canadian-born women reported significantly more psychosocial risk factors compared to immigrant women. The best predictors of postpartum depressive symptoms at 8-weeks among Canadian-born women included psychosocial risk, prenatal anxiety and depressive symptoms as well as early postpartum depressive symptoms. Prenatal somatic symptoms predicted postpartum depressive symptoms among recent immigrants. Depressive symptoms at 1-week postpartum and the lack of an emotionally supportive partner were significant predictors of postpartum depressive symptoms for both Canadian-born and immigrant women. Discussion: There appears to be both overlapping and distinct predictors of postpartum depressive symptoms for immigrant and Canadian-born women. Conclusion: The findings from this research will help guide routine screening options and patient-centered approaches to management of perinatal depression for diverse populations.